2017
DOI: 10.1111/mmi.13754
|View full text |Cite
|
Sign up to set email alerts
|

The proteome and transcriptome of the infectious metacyclic form of Trypanosoma brucei define quiescent cells primed for mammalian invasion

Abstract: Summary The infectious metacyclic forms of Trypanosoma brucei result from a complex development in the tsetse fly vector. When they infect mammals, they cause African sleeping sickness in humans. Due to scarcity of biological material and difficulties of the tsetse fly as an experimental system, very limited information is available concerning the gene expression profile of metacyclic forms. We used an in vitro system based on expressing the RNA binding protein 6 to obtain infectious metacyclics and determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
104
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(115 citation statements)
references
References 94 publications
(131 reference statements)
11
104
0
Order By: Relevance
“…In addition, we cannot rule out that the undetermined VSG repertoire of the TSW-196 strain 77 (used in this study) could be different to that from other strains 78 . Importantly, previous studies have found similar results although this aspect has been overlooked 34,36,64,74 (Supplementary Table 3). For example, at least two BSF VSGs were identified in saliva from flies infected with T. b. brucei EATRO 1125 34 ; one BSF vsg was found to be highly transcribed in a T. b. brucei RUMP503 SG infection 64 ; and 15 BSF vsg s had similar transcription levels than mvsg s (and a few were detected as protein) in T. b. brucei Lister 427 MCF overexpressing the RNA-binding protein 6 74 .…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In addition, we cannot rule out that the undetermined VSG repertoire of the TSW-196 strain 77 (used in this study) could be different to that from other strains 78 . Importantly, previous studies have found similar results although this aspect has been overlooked 34,36,64,74 (Supplementary Table 3). For example, at least two BSF VSGs were identified in saliva from flies infected with T. b. brucei EATRO 1125 34 ; one BSF vsg was found to be highly transcribed in a T. b. brucei RUMP503 SG infection 64 ; and 15 BSF vsg s had similar transcription levels than mvsg s (and a few were detected as protein) in T. b. brucei Lister 427 MCF overexpressing the RNA-binding protein 6 74 .…”
Section: Discussionsupporting
confidence: 69%
“…The identification of mVSG peptides in infected saliva is not surprising given that infected SGs contain thousands of quiescent metacyclic cells, which may release mVSGs into the SG lumen. mVSG release may occur partly by the action of the parasite GPI-PLC, which is highly expressed in MCFs 21,74 and/or by the action of tsetse salivary proteases. Interestingly, among the VSG species detected, only one corresponds to a canonical mVSG (mVAT4), which has not been previously detected as protein, but its MES has been well characterized 75 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3'-UTRs of these mRNAs have, respectively, two, five, and seven copies of the RBP10 consensus recognition motif ( Fig 1A). All three mRNAs are more abundant, and considerably better translated, in procyclic forms than in growing bloodstream forms , Dejung et al, 2016, Jensen et al, 2014, Antwi et al, 2016, and their expression is also lower in metacyclic forms than in procyclic forms (Christiano et al, 2017). When ZC3H20 or ZC3H21 are tethered (via a lambdaNpeptide -boxB interaction) to a reporter mRNA in bloodstream forms, expression is stimulated, whereas tethering of ZC3H22 leads to repression (Lueong et al, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…The 3′‐UTRs of these mRNAs have, respectively, two, five and seven copies of the RBP10 consensus recognition motif (Figure a). All three mRNAs are more abundant, and considerably better translated, in procyclic forms than in growing bloodstream forms (Antwi et al, ; Dejung et al, ; Fadda et al, ; Jensen et al, ), and their expression is also lower in metacyclic forms than in procyclic forms (Christiano et al, ). When ZC3H20 or ZC3H21 are tethered (via a lambdaN‐peptide–boxB interaction) to a reporter mRNA in bloodstream forms, expression is stimulated, whereas tethering of ZC3H22 leads to repression (Erben, Fadda, Lueong, Hoheisel, & Clayton, ; Lueong, Merce, Fischer, Hoheisel, & Erben, ).…”
Section: Introductionmentioning
confidence: 99%